The cinematographic representation of social frames - Bejko, Julian (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The author of the essay titled «The Cinematographic Representation of Social Frames» analyzes images in the context of representing physical and ontological aspects of reality. He considers Albanian Communist Cinema (1952–1991) taking into consideration the viewer’s perspective in which cinema is treated as a metaphorical place when people learn to read images and can think through images. The author also focuses on following issues: processes of individualization, representation and the problematisation of subjectivity.